2014
DOI: 10.1167/iovs.13-13229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Contrast Adaptation in Glaucoma and in Aging

Abstract: Glaucoma alters rapid contrast adaptation while aging does not. Contrast adaptation is key to visual processing in natural visual environments. Our results imply that glaucoma produces abnormalities in natural visual experiences in central vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Additionally, as previously noted, care needs to be taken in interpreting PVEP signals as its contributions are not limited to V1. 18,57,63 In this study, glaucoma participants demonstrated flatter retinal contrast response functions, a finding consistent with elevated contrast discrimination thresholds 14,28,67 and reduced contrast gain signatures found in perceptual studies. [14][15][16] The PERG magnitude loss (~52%) in our early glaucoma cohort was of a similar extent as compared to previous studies, 41,42,68,69 and is likely due to retinal ganglion cell loss 7 or dysfunction 70,71 in glaucoma.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, as previously noted, care needs to be taken in interpreting PVEP signals as its contributions are not limited to V1. 18,57,63 In this study, glaucoma participants demonstrated flatter retinal contrast response functions, a finding consistent with elevated contrast discrimination thresholds 14,28,67 and reduced contrast gain signatures found in perceptual studies. [14][15][16] The PERG magnitude loss (~52%) in our early glaucoma cohort was of a similar extent as compared to previous studies, 41,42,68,69 and is likely due to retinal ganglion cell loss 7 or dysfunction 70,71 in glaucoma.…”
Section: Discussionsupporting
confidence: 87%
“…23 Studies in older adults have shown that aging can result in neurological alterations at the retina including the loss of retinal ganglion cells, 24,25 as well as at the LGN 26 and visual cortex, 27 the same sites that undergo neurodegeneration in glaucoma. Healthy aging alters a range of perceptual contrast effects, including contrast detection, 28,29 contrast discrimination, 28 spatial contrast suppression 30,31 and contrast gain signatures. 32 Such perceptual effects are consistent with changes to both structural and neurochemical changes in the senescent visual system (for review, see McKendrick et al 33 ) In many ophthalmic conditions, the effects of aging and the effects of disease appear along a continuum.…”
mentioning
confidence: 99%
“…Very few studies have investigated these aspects of visual function in older adults. Current available data suggests that rapid contrast adaptation is similar between age groups for briefly presented grating stimuli . The question of whether slow contrast adaptation differs between older and younger people does not appear to have been tested directly, however, performance measured in older adults appears at least qualitatively similar to separate reports collected in younger adults …”
Section: The Ageing Eyementioning
confidence: 93%
“…Glaucoma was associated with a reduction in contrast detection and discrimination adaptation in the early stages. 27 Reduction of visual acuity or contrast sensitivity caused slower reading speed in glaucoma. 28 Our findings might suggest that reading speed reduction in the early stages of glaucoma might be just transient evidence of coping mechanisms being established.…”
Section: Discussionmentioning
confidence: 99%